Implementasi Produksi Event Studi Kasus Loading In & Loading Out Pada Event Pancaverse - Lazia Putri Widjiastuti; Mochamad Amboro Alfianto; Akwilla Nathanael Odoh; M. Alandra Bestama; Gilang Ramadan; Arif Ramdhani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The loading in and loading out processes are crucial stages in event production. Although often invisible to the audience, they have a direct impact on the smooth running and quality of the event. This study aims to examine the implementation of the loading process at the Pancaverse event held at Depok City Square, focusing on technical dynamics, field challenges, and the implemented solution strategies. This study uses a descriptive qualitative approach through a case study, where data was obtained through field observations, in-depth interviews with five key informants, and technical documentation of the event. The results show that the success of the loading process is highly dependent on several key factors, including detailed planning, clear work zone division, and responsive inter-team communication. Thorough planning before the event begins is crucial to minimize technical errors during the loading process. Furthermore, a structured work zone division facilitates coordination between teams and accelerates workflow. Effective communication between teams, both internally and with external parties, also significantly influences the smooth running of the loading process. However, external factors such as bad weather and miscommunication between vendors are major challenges faced. These challenges can impact the smooth logistics and the overall loading process. Therefore, risk mitigation is carried out through cross-checking logistics, intensive coordination with external parties, and providing backup plans in case of obstacles. The use of a logistics checklist and tagging system has also proven effective in accelerating the identification of goods during unloading, thereby streamlining the loading and unloading process. Overall, this study emphasizes the importance of technical and managerial readiness in handling the loading process as an integral part of event production. These findings are expected to provide practical insights for event industry players in designing and implementing more adaptive and efficient logistics strategies in the field.